Pushing the Button: One Speech-Language Pathologist Researcher's Journey to Operating a Fluoroscope for Swallow Studies - Jones, Corinne A (Journal of speech, language, and hearing research, 2025)
Videofluoroscopy is an invaluable tool in the study of swallowing physiology. It is not without risks, however, primarily from exposure to ionizing radiation. As such, regulation across states within the United States and institutional policies are in place to protect patients, research participants, and occupational users from the negative effects of radiation exposure. These regulations restrict those who can "push the button" to energize the x-ray machines during radiographic studies, typically to licensed physicians and radiologic technologists. While recognizing the importance of limiting risks associated with radiation exposure, these personnel requirements add logistical burden to speech-language pathologist researchers who perform videofluoroscopic swallow studies in their laboratories. In this article, I discuss my process to obtaining authorization to operate my laboratory's C-arm fluoroscope for research swallow study procedures. While state and institutional regulations differ, I hope that the detailing of this process will aid other research groups to advocate for more independence in performing research videofluoroscopic procedures.